2006
DOI: 10.1182/blood-2005-11-007591
|View full text |Cite
|
Sign up to set email alerts
|

A novel fibrinogen variant (fibrinogen Seoul II; AαGln328Pro) characterized by impaired fibrin α-chain cross-linking

Abstract: We report a novel fibrinogen variant (fibrinogen Seoul II), which has a heterozygous point mutation from CAA to CCA leading to A␣Gln328Pro. The mutation site is among several glutamine residues that serve as ␣-chain cross-linking acceptor sites. Fibrinogen Seoul II was found in a 51-year-old male patient and his family in Seoul, Korea. The patient was diagnosed with myocardial infarction at age 43. Eight years later he was admitted to the emergency room due to recurrence of the disease, where he expired under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Previous investigations, however, have shown that Q328 is an important reactive glutamine. 22,40 In our assay, we were able to characterize Q328 following a chymotrypsin digest. Our ability to monitor all three reactive glutamines simultaneously in aC (233-425) is enhanced by digesting each sample time point separately with chymotrypsin and GluC (Figure 1).…”
Section: Org Frommentioning
confidence: 97%
See 1 more Smart Citation
“…Previous investigations, however, have shown that Q328 is an important reactive glutamine. 22,40 In our assay, we were able to characterize Q328 following a chymotrypsin digest. Our ability to monitor all three reactive glutamines simultaneously in aC (233-425) is enhanced by digesting each sample time point separately with chymotrypsin and GluC (Figure 1).…”
Section: Org Frommentioning
confidence: 97%
“…32,33,39 Fibrinogen Seoul II (Q328P mutation) exhibits impaired fibrin polymerization and a reduced extent of a-a crosslinking due in part to the loss of a reactive glutamine within the aC region. 40 Several studies have identified specific crosslinking sites in the aC region responsible for lateral aggregation, but little is known about the individual reactive glutamines and the roles played by the surrounding residues. 17,18,20,22,23,41,42 Antibody studies by Procyk et al identified a FXIIIa binding site within aC (242-424) and then narrowed the site more specifically to aC (389-402).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations, however, have shown that Q328 is an important reactive glutamine. 68,81 In this assay, we were able to characterize Q328 following a chymotrypsin digest. The ability to monitor all three reactive glutamines simultaneously in αC (233-425) is enhanced by digesting each sample time point separately with chymotrypsin and Glu C (Figure 23).…”
Section: 72mentioning
confidence: 97%
“…Truncations and mutations in this region have also been correlated with disease conditions associated with IDPs. 68,70 Furthermore, many of the reactive glutamines crosslinked by Factor XIIIa are located in loop and flexible regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation